2021
DOI: 10.3390/pharmaceutics13122111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bariatric Surgery and Gastrectomy on the Absorption of Drugs, Vitamins, and Mineral Elements

Abstract: Bariatric surgery, which is an effective treatment for obesity, and gastrectomy, which is the primary treatment method for gastric cancer, alter the anatomy and physiology of the digestive system. Weight loss and changes in the gastrointestinal tract may affect the pharmacokinetic parameters of oral medications. Both bariatric and cancer patients use drugs chronically or temporarily. It is important to know how surgery affects their pharmacokinetics to ensure an effective and safe therapy. The Cochrane, PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The powdered form was more effective because it is absorbed through the lining of the small intestine at a faster rate and bypasses the need for the breakdown of a pill or capsule. A 2021 cross-sectional study found that bariatric surgery reduces the time to maximal plasma concentration (Tmax) and the maximum plasma concentration (Cmax) of most drugs and vitamins [ 6 ]. Therefore, while the small intestine is able to absorb the drug more rapidly, it ultimately absorbs less of it, thus significantly decreasing serum drug concentration [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powdered form was more effective because it is absorbed through the lining of the small intestine at a faster rate and bypasses the need for the breakdown of a pill or capsule. A 2021 cross-sectional study found that bariatric surgery reduces the time to maximal plasma concentration (Tmax) and the maximum plasma concentration (Cmax) of most drugs and vitamins [ 6 ]. Therefore, while the small intestine is able to absorb the drug more rapidly, it ultimately absorbs less of it, thus significantly decreasing serum drug concentration [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 cross-sectional study found that bariatric surgery reduces the time to maximal plasma concentration (Tmax) and the maximum plasma concentration (Cmax) of most drugs and vitamins [ 6 ]. Therefore, while the small intestine is able to absorb the drug more rapidly, it ultimately absorbs less of it, thus significantly decreasing serum drug concentration [ 6 ]. In our patient’s case, her Cmax for absorption of the oral potassium pill was likely similarly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been established that the metabolism of tacrolimus depends on the individual predispositions, such as BMI (body mass index), patient’s age, albumin concentration or hepatic failure [ 1 ]. Tacrolimus is mainly metabolised by the cytochrome P450 (CYP450) isoform CYP3A4, which is involved in the metabolism of a number of substances, such as beverages, alcohol, herbs, medications and food [ 6 ]. Nevertheless, these substances may be the inducers or inhibitors of the abovementioned enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery is an effective weight management strategy that has been demonstrated to improve overall survival, mitigate the effects of cardiovascular and metabolic diseases (including diabetes and hyperlipidemia), and reduce cancer risk and cancer‐related mortality 1,2 . The procedures can be broadly classified as those that are primarily restrictive of the amount of food stored in the stomach but not interfering with normal digestion (e.g., sleeve gastrectomy and gastric banding), those that limit absorption by shortening the gastrointestinal tract (e.g., biliopancreatic diversion), and those that combine both mechanisms (e.g., Roux‐en‐Y gastric bypass) 3 . Thus, depending on the type of procedure, the absorption of medications, including oral chemotherapy agents, may be affected in different ways.…”
mentioning
confidence: 99%
“…1,2 The procedures can be broadly classified as those that are primarily restrictive of the amount of food stored in the stomach but not interfering with normal digestion (e.g., sleeve gastrectomy and gastric banding), those that limit absorption by shortening the gastrointestinal tract (e.g., biliopancreatic diversion), and those that combine both mechanisms (e.g., Roux-en-Y gastric bypass). 3 Thus, depending on the type of procedure, the absorption of medications, including oral chemotherapy agents, may be affected in different ways. Bariatric surgery alters gastric mixing and disintegration of food and medications, decreases gastric acid secretion and thus results in an increased pH, accelerates gastric transit time via hormonal and neural influences, changes the enterohepatic recirculation of bile acids in the upper intestine, reduces the functional gastrointestinal tract absorptive area, and alters drug metabolism by bypassing the parts of the small intestine that contain a high abundance of cytochrome P450 isoenzymes.…”
mentioning
confidence: 99%